1962
DOI: 10.1017/s0079497x00015747
|View full text |Cite
|
Sign up to set email alerts
|

Excavations at Shearplace Hill, Sydling St. Nicholas Dorset, England

Abstract: SummaryThis report describes the excavation of a small complex of earthworks on the Dorset chalk upland (fig. 1) associated with fields and droveways. Several banked and ditched enclosures were present, the main one of which contained two sub-circular houses. The lay-out of these houses may be ascribed largely to the Deverel-Rimbury occupation of the site, but the main earthworks of the farmstead are dated on the evidence of the pottery to the early Middle Bronze Age, if not to the Wessex Bronze Age. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Such sizeable, double-ring, post-built structures with porches are more often associated with the succeeding millennium and the Iron Age (for which considerable examples are recorded), although porched Bronze Age examples do exist (eg among the several structures excavated at Black Patch in Sussex, where the outer walls are considered to have been founded on spreads of flint nodules (Drewett 1979;. There are more conventional, large, double-ring post built structures of Bronze Age date from a number of sites in England, of which the most celebrated southern examples are at Itford Hill (Burstow & Holleyman 1957) and Shearplace Hill (Rahtz & ApSimon 1962), both in Sussex. More recently the site of Paddock Hill, Thwing, Yorkshire revealed a substantial double-ring circular structure set centrally within an enclosure of Bronze Age date (Bewley 1994, 82, fig 51).…”
Section: Discussion Neolithic Pitsmentioning
confidence: 99%
“…Such sizeable, double-ring, post-built structures with porches are more often associated with the succeeding millennium and the Iron Age (for which considerable examples are recorded), although porched Bronze Age examples do exist (eg among the several structures excavated at Black Patch in Sussex, where the outer walls are considered to have been founded on spreads of flint nodules (Drewett 1979;. There are more conventional, large, double-ring post built structures of Bronze Age date from a number of sites in England, of which the most celebrated southern examples are at Itford Hill (Burstow & Holleyman 1957) and Shearplace Hill (Rahtz & ApSimon 1962), both in Sussex. More recently the site of Paddock Hill, Thwing, Yorkshire revealed a substantial double-ring circular structure set centrally within an enclosure of Bronze Age date (Bewley 1994, 82, fig 51).…”
Section: Discussion Neolithic Pitsmentioning
confidence: 99%
“…PhD research carried out by one of the authors (Brück 1997) on Middle Bronze Age settlements in southern England identified jet-like objects at only four out of 65 sites, and no amber objects at all. These derived from contexts similar to some Late Bronze Age settlements: at Shearplace Hill in Dorset, for example, a post-hole that formed part of the main post-ring of roundhouse A produced an armlet core, while an armlet fragment was found just to the rear of this building in slip from the bank surrounding the settlement (Rahtz & ApSimon 1962, 323). In comparison to this small dataset, there is a significantly increased quantity of material from the Late Bronze Age.…”
Section: Conclusion: the Social Agency Of Objectsmentioning
confidence: 99%